Editorial - Joanna Krasodomska; Nadia Albu; Anna Szychta (Zeszyty Teoretyczne Rachunkowości)
Dear Authors and Readers, vol. 48, number 4 of “Zeszyty Teoretyczne Rachunkowości” (ZTR, “The Theoretical Journal of Accounting”) includes articles in English accepted for the special issue of ZTR in 2024, entitled Sustainable Development, Accounting, and Accountants. This issue also contains a review of the collective work entitled Handbook of Accounting, Accountability and Governance, edited by Garry D. Carnegie and Christopher J. Napier, as well as a list of reviewers of articles in ZTR in 2024. Starting in 2012, this marks the 13th thematic issue of ZTR in English. The papers featured in this issue focus on the theme of sustainable development. The shifting landscape, marked by recent sustainability reporting regulations such as the European Union’s Corporate Sustainability Reporting Directive (CSRD), the European Sustainability Reporting Standards (ESRS), and the global standards introduced by the International Sustainability Standards Board (ISSB), has the potential to drive significant transformation in both the practice and teaching of accounting. Together, the papers in this Special Issue provide valuable insights into the intersection of accounting, sustainability, regulation, and education, highlighting the challenges and opportunities faced by those navigating the evolving landscape of sustainability reporting. Sustainable Development Goals (SDGs) are central to the United Nations’ Agenda 2030, which outlines a global framework for achieving sustainable development across economic, social, and environmental dimensions. Arleta Szadziewska, Anna Szychta, and Halina Waniak-Michalak examine how companies listed on the Warsaw Stock Exchange (WSE) communicate their commitment to the SDGs, using indicators proposed by the Intergovernmental Working Group of Experts on International Accounting and Reporting Standards (UNCTAD-ISAR). Through a content analysis of 235 reports from 2019 to 2022, their study reveals a gap between companies’ declared commitments to the SDGs and their actual disclosures. The research identifies company size, industry type, and the number of declared SDGs as key factors that influence the extent of SDG reporting. In contrast, the reporting standards used (e.g., GRI) did not significantly affect disclosure levels. Hanna Mysaka and Ivan Derun conducted a bibliometric analysis of the theoretical frameworks underlying sustainability reporting (SR) and non-financial reporting (NFR) within the context of EU regulatory changes. Their analysis shows that SR has become the dominant framework in shaping EU corporate reporting regulations, both quantitatively and qualitatively. Their study underscores the need for further development in the NFR domain, highlighting the underdevelopment of its theoretical framework as a key factor hindering the effectiveness of the EU’s non-financial reporting regulations. Materiality analysis serves as a fundamental pillar of sustainability reporting. Mohamed Anas Belidan and Halima Baghad provide a scoping review of the theoretical foundations of materiality in sustainability reporting, comparing single and double materiality approaches. Their findings highlight a growing emphasis on double materiality, driven by evolving stakeholder expectations and regulatory mandates. The authors argue that harmonizing reporting standards and fostering active stakeholder engagement are crucial for enhancing the quality and consistency of sustainability disclosures. Paweł Szalacha’s study also focuses on the concept of materiality, examining the implementation of double materiality by early adopters among Polish companies. Using 2023 sustainability reports as empirical data, he finds that integrating double materiality into sustainability reporting has brought changes to the content of reports and the disclosure of materiality determination processes. The study identifies key drivers behind these changes and highlights reporting gaps, offering valuable insights into the challenges companies face in implementing double materiality. The CSRD introduces mandatory sustainability assurance at a limited level; however, some companies already have experience in this area through voluntary practices. Małgorzata Macuda and Paweł Zieniuk analyze voluntary assurance practices in European companies’ sustainability reports prior to the CSRD’s implementation. Their research, based on a sample of 576 companies, shows that the decision to seek voluntary assurance was influenced by company-specific factors, prior experience in sustainability reporting, and the strength of auditing standards in the country. Their study provides valuable insights into the extent of voluntary assurance practices before the introduction of mandatory assurance requirements under the CSRD. Finally, a new approach to accounting education is needed to better align with this evolving context. The paper by Abdel K. Halabi, Alan Labas, and Craig Hurley explores whether introducing a transformative subject on sustainability, the environment, and the SDGs into a master’s accounting course can foster critical thinking and shift student attitudes. Using qualitative data from student reflective journals, analyzed thematically through NVIVO software, the findings reveal transformative outcomes, including changed atti-tudes, increased self-efficacy to drive positive change, enhanced critical thinking, and a deeper understanding of business impacts on the environ-ment. Most students expressed a preference for working in environmentally responsible businesses. The research addresses a gap by highlighting account-ing students’ perspectives on sustainability-related issues and supports calls to redefine accounting beyond technical practice. The Reviews section of this issue of ZTR contains a review of Handbook of Accounting, Accountability and Governance, a collective work published in the “Research Handbooks on Accounting” series by Edward Elgar Publishing in 2023. This comprehensive publication, edited by eminent professors of accounting Garry D. Carnegie and Christopher J. Napier, is a compendium of knowledge on the interconnections between accounting, accountability, and governance. It includes an Introduction and 21 chapters authored by 45 specialists in the fields of accounting, accountability, and governance. The Handbook is a valuable source of information for researchers and doctoral students about the history, present and possible future of the triad of issues expressed in the title of this work. We are pleased to announce that the Editorial Team of ZTR has completed a project under the “Development of scientific journals” program for the period 4 October 2022 – 4 October 2024 (Agreement RCN/SP/0062/2021/1; funding from the Ministry: PLN 80,000, total project amount: PLN 122,560). The final report was submitted to the Ministry of Science and Higher Education in November 2024. All planned activities were completed on time. During the implementation of the project, eight issues of ZTR were prepared for publication and published, containing 77 articles: 41 in English and 36 in Polish. Of the 41 articles in English, 19 were published in two thematic issues (Vol. 46, No. 4 in 2022 and Vol. 47, No. 4 in 2023), while the remaining 22 articles were included in the six other issues of ZTR published in 2023 and 2024. The Editorial Team would like to thank all the reviewers of ZTR articles so far, especially the 71 specialists who provided anonymous reviews and insightful feedback in 2024. The list of Polish and foreign reviewers is included in this issue of ZTR and on the website of our journal https://ztr.skwp.pl/cms/reviewers. We would also like to thank all the authors of articles published in the four issues of ZTR in 2024 for their cooperation with the Editorial Team. We encourage authors and readers to visit ZTR’s website at https://ztr.skwp.pl/, where you can find a lot of information about the journal, including its objectives and scope, publication ethics, principles of reviewing, accepting, and preparing articles, and the procedures for submitting a paper to the journal. Polish and foreign authors are invited to submit interesting papers for future issues of ZTR, including a thematic issue in 2025 entitled Contemporary chal-lenges, conditions, and directions of development of accounting (for more, see Call for papers published in ZTR, Vol. 48, No. 2 and at https://ztr.skwp.pl/cms/CMS:647). On behalf of the entire ZTR Editorial Team, we wish all authors, reviewers, members of the Editorial Board, and readers of ZTR a lot of health, happiness, and peace, as well as numerous professional successes in 2025. We hope that all your plans come to fruition. Yours faithfully Joanna Krasodomska, Nadia Albu, Anna Szychta